Toxic content and user engagement on social media: Evidence from a field experiment - George Beknazar-Yuzbashev; Rafael Jiménez Durán; Jesse McCrosky; Mateusz Stalinski (University of Chicago Booth School of Business, Stigler Center for the Study of the Economy and the State, 2025)
Most social media users have encountered harassment online, but there is scarce evidence of how this type of toxic content impacts engagement. In a pre-registered browser extension field experiment, we randomly hid toxic content for six weeks on Facebook, Twitter, and YouTube. Lowering exposure to toxicity reduced advertising impressions, time spent, and other measures of engagement, and reduced the toxicity of user-generated content. A survey experiment provides evidence that toxicity triggers curiosity and that engagement and welfare are not necessarily aligned. Taken together, our results suggest that platforms face a trade-off between curbing toxicity and increasing engagement
Keywords: C93; D12; D83; D90; I31; L82; L86; M37; Z13; 330; toxic content; moderation; social media; user engagement; browser experiment